The placebo response and the power of unconscious healing - Kradin, Richard L. (Routledge, 2008)
Placebo responses are automatic and unconscious and cannot be predicted on conscious volition. Instead, they reflect complex interactions between the innate reward system of the nervous system and encoded procedural memories and imaginal fantasies. This book contributes therapeutic effects, varies in potency, and exhibits its own pathologies.